Characteristics of the Market Value of Undeveloped Land in Health Resort Municipality of Kolobrzeg - Lazarek-Janowska, Magdalena; Czajka, Agnieszka (European Scientific Journal, ESJ, 2017)
The article presents a statistical analysis of selected properties of undeveloped real estate market in the municipality of Kolobrzeg. The municipality of Kolobrzeg is located in the West Pomeranian Vivodeship in the north-western part of Poland. Municipality of Kolobrzeg is mainly a health resort region utilising natural resources. The study has been conducted within the administrative boundaries of the municipality of Kolobrzeg between 2008-2014. The results of the study were examined using the multiple regression analysis method. The following attributes of the real estates were taken into consideration when conducting the aforementioned analysis: the price, size, location and environmental conditions.The analysis presented in this article is just a portion of a larger scale research conducted by the authors which will further be expanded upon.